Assessing Community Health: An Innovative Tool for Measuring Height and Length. (30th June 2017) - Bauman, Ashley; Ernst, Kacey; Hayden, Mary; Roe, Denise J; Murray, Rachel; Agawo, Maurice; Munga, Stephen; Schmahl, Erik; Taren, Douglas
Abstract: Anthropometric measurements, including height and length, are routinely needed for health research worldwide. Measurement boards are the current gold standard for obtaining the height and length of children. In community-based research, however, the size and weight of the measurement boards make them difficult and cumbersome to carry in the field. In addition, children and infants may express an unwillingness to be placed onto the measurement board. Electronic measuring tools commonly used in industry and contracting work are precise and portable. This study piloted a protocol to use an adapted laser measurement tool, the anthropometric measurement assist (AMA), to obtain height and recumbent length in children in Western Kenya. Intra- and inter-observer variability were determined and compared with measurement board measurements. Results of this initial pilot indicated that the AMA may be a viable alternative to measurement boards. The AMA can measure height/length accurately and reliably, is portable and is equivalent in price to measuring boards, making it a viable option for fieldwork in low-resourced countries.